Tren Inovasi Pembelajaran Dalam Kegiatan Pengabdian Masyarakat LPTK Di Indonesia: Dari Pendampingan Klasikal Hingga Ekosistem Literasi Digital - Gunawan, Gunawan; Herayanti, Lovy; Ahmadi, Ahmadi; Yahya, Fahmi (Indonesian Publication Center, 2024)
Teacher Training Institutions (LPTK) play a strategic role in transforming educational quality through community service. This article aims to analyze the trends of learning innovation within LPTK service programs in Indonesia during the 2019-2023 period. Based on a literature review of 38 selected references, a significant shift in the mentoring paradigm was identified. Initially, community service focused on classical approaches such as Lesson Study, Classroom Action Research (CAR), and conventional media development. However, driven by post-pandemic demands, the trend has shifted towards establishing comprehensive digital literacy ecosystems. These innovations include the integration of Artificial Intelligence (AI), Augmented Reality (AR), Learning Management Systems (LMS), and digital parenting programs. The analysis reveals that LPTKs are no longer solely focused on teachers' technical skills in the classroom but are actively building synergy between schools, families, and technology to create a sustainable digital learning ecosystem.